PENGARUH SISTEM ISYARAT BAHASA INDONESIA (SIBI) BERITA TELEVISI TERHADAP PEMAHAMAN INFORMASI SISWA TUNARUNGU DI KOTA PEKANBARU - Yeni Reskina; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Indonesian Language Signaling System (SIBI) is one of the media that helps communication of deaf people in the wider community. Its form is a systematic order of a set of finger, hand and various gestures that symbolize the vocabulary of sign language. SIBI on news programs can help deaf people to understand and get news information. The theory used in this study is the Stimulus - Response theory. The purpose of this study was to determine how much influence the Indonesian language signal system (SIBI) television news had on understanding information on deaf students in Pekanbaru.This research uses quantitative research methods, with data collection techniques, namely through questionnaires with a total sample of 50 deaf students which is determined through purposive sampling techniques.The results of this study indicate that the degree of influence of the Indonesian Language Signal System (SIBI) on the Understanding of Information on Deaf Students in Pekanbaru City is Y = -1,269 + 0,713X + e. The constant number is -1,269 and the SIBI variable coefficient is 0,713, while t count 10,048 is greater than t table 2,011 with a significance level of 0,000 smaller than α = 0,05. Based on the "Model Summary" table shows that the value of R = 0.823 and the coefficient of determination (R square) obtained is 0.678 as a result of the squared correlation coefficient 0.823 x 0.823. This figure shows the understanding that the influence of the Indonesian language signal system (SIBI) on television news on information comprehension of deaf students in pekanbaru city is 67.8%. While the remaining 32.2% is influenced by other variables not included in this study. This means that the Indonesian language signal system (SIBI) television news has a strong influence of 67.8% on understanding information on deaf students in Pekanbaru.